Legal identity, race and belonging in the Dominican Republic : from citizen to foreigner - Hayes de Kalaf, Eve (Anthem series in citizenship and national identities., 2022)
This book provides a cautionary tale regarding legal identity practices as promulgated by the World Bank, UN and Inter-American Development Bank. It warns that policies encouraging the en masse registration of native-born migrant-descended populations can also force the thorny question of nationality, unsettling long-established identities and entitlements.